Identification of biosynthetic genes for the β-carboline alkaloid kitasetaline and production of the fluorinated derivatives by heterologous expression. (1st May 2019) - Ueda, Shohei; Ikeda, Haruo; Namba, Takushi; Ikejiri, Yukinori; Nishimoto, Yuri; Arai, Masayoshi; Nihira, Takuya; Kitani, Shigeru
Abstract: β-Carboline alkaloids exhibit a broad spectrum of pharmacological and biological activities and are widely distributed in nature. Genetic information on the biosynthetic mechanism of β-carboline alkaloids has not been accumulated in bacteria, because there are only a few reports on the microbial β-carboline compounds. We previously isolated kitasetaline, a mercapturic acid derivative of a β-carboline compound, from the genetically modified Kitasatospora setae strain and found a plausible biosynthetic gene cluster for kitasetaline. Here, we identified and characterized three kitasetaline ( ksl ) biosynthetic genes for the formation of the β-carboline core structure and a gene encoding mycothiol- S -conjugate amidase for the modification of the N -acetylcysteine moiety by using heterologous expression. The proposed model of kitasetaline biosynthesis shows unique enzymatic systems for β-carboline alkaloids. In addition, feeding fluorotryptophan to the heterologous Streptomyces hosts expressing the ksl genes led to the generation of unnatural β-carboline alkaloids exerting novel/potentiated bioactivities.